Analisis Miskonsepsi Mahasiswa dalam Memahami Pembagian Jamur Makroskopis dan Jamur Mikroskopis serta Pemisahan Antara Lichenes dengan Fungi pada Mahasiswa Pendidikan Biologi di UIN Sumatera Utara - Widya Ulfa, Syarifah; Nasution, Aziz Husein; Purba, Balqis Putri Wardana; Mawaddah, Hanifa; Hafizhah, Kayla Nur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the misconceptions of students in understanding the division of macroscopic fungi and microscopic fungi and the separation between Lichenes and Fungi in Biology Education students at UIN North Sumatra. This research was conducted at the State Islamic University of North Sumatra, to be precise in the TBIO-2 class of Stambuk 2021 Academic Year 2023/2024. Using descriptive qualitative research methods and conducting interviews as a data collection method. The results showed that many biology students have a wrong understanding, such as thinking that all macroscopic fungi can be seen with the naked eye and microscopic fungi can only be observed with a microscope. The misunderstanding is because the curriculum does not emphasize specific characteristics, such as some macroscopic fungi require a microscope for certain observations. Thus, it is necessary to improve understanding, which can be achieved through the development of comprehensive teaching materials, interactive methods, and continuous training.